Impact of Remote Work Readiness and Digital Wellbeing on Work Engagement, Moderated by Generational Tech Gap - Amiruddin Qadaar; Melli Andini; Faidal; Reza Rahmadi Hasibuan (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
This study investigates the influence of digital wellbeing and remote work readiness on employee work engagement in micro, small, and medium enterprises (MSMEs) located in tourist destinations, while considering the moderating role of the generational tech gap. Drawing upon the Job Demands–Resources (JD-R) theory, the study surveyed 388 employees using stratified sampling and analyzed the data through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that both digital wellbeing and remote work readiness significantly enhance work engagement. Additionally, the generational tech gap directly affects engagement but does not moderate the relationship between the independent variables and engagement. These results suggest that digital competencies and psychological health are critical across generations, although generational differences still independently matter. The study advances JD-R theory by incorporating digitally relevant constructs and offers practical implications for MSME managers to implement digital wellbeing programs and inclusive training policies. Limitations include its cross-sectional design and reliance on self-reported data. Future research should adopt longitudinal approaches and explore sectoral comparisons to deepen the understanding of digital engagement dynamics.